1991
DOI: 10.3177/jnsv.37.573
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maternal Supplementation with Linoleic and .GAMMA.-Linolenic Acids on the Fat Composition and Content of Human Milk: A Placebo-Controlled Trial.

Abstract: SummaryTotal fat content and therefore total energy content and the content of essential fatty acids (EFAs) in milk are known to decline with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Our results are in accordance with previous supplementation studies in healthy subjects. Administration of either evening primrose oil or blackcurrant seed oil (both rich in GLA) raised the levels of GLA and DGLA (Rassias & Gibson, 1988), and supplementation with evening primrose oil for 2 ± 6 months increased the breast milk level of GLA and DGLA, but not AA (Cant et al, 1991). Therefore, it is unlikely that the absence of an increase in AA in our study is due to the short duration of supplementation or to a disturbance of fatty acid metabolism related to atopy of the mother.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in accordance with previous supplementation studies in healthy subjects. Administration of either evening primrose oil or blackcurrant seed oil (both rich in GLA) raised the levels of GLA and DGLA (Rassias & Gibson, 1988), and supplementation with evening primrose oil for 2 ± 6 months increased the breast milk level of GLA and DGLA, but not AA (Cant et al, 1991). Therefore, it is unlikely that the absence of an increase in AA in our study is due to the short duration of supplementation or to a disturbance of fatty acid metabolism related to atopy of the mother.…”
Section: Discussionmentioning
confidence: 99%
“…The dosage of GLA was reported to be physiological amounts (100 mg/day) as found in healthy non-atopic individuals and yet it did not produce any significant change in maternal milk fatty acid content, nor did it alter the infant erythrocyte fatty acid composition. Historically, maternal supplementation with 320 mg of GLA per day from EPO increased milk AA levels by up to 8% [57] and more recent studies have confirmed that milk polyunsaturated fatty acid (PUFA) content influences the composition of infant serum phospholipids [41].…”
Section: Speculative Debatementioning
confidence: 99%
“…19,41,43 There have been cases in which evening primrose oil appears to have exacerbated epilepsy. Drugs that may interact adversely with evening primrose include phenothiazines, 37,39,44 nonsteroidal anti-inflammatory drugs, corticosteroids, 45 ␤-blockers, 39 and anticoagulants. 43 …”
Section: Evening Primrosementioning
confidence: 99%